The Savvy Survey #18: Group-Administered Surveys - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS, 2016)
This publication provides an overview of group-administered surveys as part of the Savvy Survey Series. Group-administered surveys are a great way to collect information from participants about the outcomes of an event or program. These kinds of surveys are best used for documenting short-term outcomes and can make use of an audience response system. This 4-page fact sheet details how to develop a group-administered questionnaire, how to use an audience response system, and how to prepare and implement the survey. Written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the Agricultural Education and Communication Department, December 2015.